2019
DOI: 10.1111/tpj.14284
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional signatures modulating shoot apical meristem morphometric and plant architectural traits enhance yield and productivity in chickpea

Abstract: Summary Plant height (PH) and plant width (PW), two of the major plant architectural traits determining the yield and productivity of a crop, are defined by diverse morphometric characteristics of the shoot apical meristem (SAM). The identification of potential molecular tags from a single gene that simultaneously modulates these plant/SAM architectural traits is therefore prerequisite to achieve enhanced yield and productivity in crop plants, including chickpea. Large‐scale multienvironment phenotyping of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Deployment of SAM morphometric characteristics in QTL mapping will target master regulators influencing simultaneously a number of correlated agronomic traits 1 3 in crops. Correlation between SAM morphometrics and WUS gene expression in governing vital agromorphological traits is recently reported in chickpea (Narnoliya et al 2019). The differential expression analysis of the CaCLV3_01 gene and its haplotypes depicted a significant increase in its expression in early-flowering desi mapping parental accession, ICC 5590 and EDTF/HFN-NIL CaHAPA line as compared to its desi counterpart ICC 6306 and LDTF/LFN-NIL CaHAPB line.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Deployment of SAM morphometric characteristics in QTL mapping will target master regulators influencing simultaneously a number of correlated agronomic traits 1 3 in crops. Correlation between SAM morphometrics and WUS gene expression in governing vital agromorphological traits is recently reported in chickpea (Narnoliya et al 2019). The differential expression analysis of the CaCLV3_01 gene and its haplotypes depicted a significant increase in its expression in early-flowering desi mapping parental accession, ICC 5590 and EDTF/HFN-NIL CaHAPA line as compared to its desi counterpart ICC 6306 and LDTF/LFN-NIL CaHAPB line.…”
Section: Discussionmentioning
confidence: 88%
“…The CLV signaling pathway is known to be associated with a number of agronomic traits such as inflorescence architecture, flower production and fruit size in tomato (Xu et al 2015). Recent studies reported the role of CLV-WUS signaling pathway-mediated stem cell regulation and related morpho-genes in modulation of the overall plant architecture (Whitewoods et al 2018;Narnoliya et al 2019). These aforesaid contextual collectively highlighted that the CLV genes are especially important SAM-mediated regulators of growth and development and thereby have potential to govern yield and architectural traits in multiple crop plants.…”
Section: Introductionmentioning
confidence: 99%
“…The axillary and inflorescence meristem, giving rise to leaves, branches and inflorescence, are derived from the SAM (Sharma and Fletcher, 2002; Yang and Jiao, 2016). The role of SAM morphometrics in regulating agronomic yield‐contributing traits is also known in crops like chickpea and maize (Basu et al ., 2019a; Leiboff et al ., 2015; Narnoliya et al ., 2019). The population of the meristematic cells is maintained through a feedback loop between the homeodomain transcription factor WUSCHEL (WUS) and its counterpart CLAVATA ( CLV ) gene family members and newly identified SQUAMOSA PROMOTER BINDING PROTEIN‐LIKE ( SPL ) family gene (Fouracre and Poethig, 2019; Somssich et al ., 2016).…”
Section: Clavata‐wuschel Signalling: Maintenance Of the Shoot Apical ...mentioning
confidence: 99%
“…Instead, it is maintained by the coordinate function of ABERRANT SPIKELET AND PANICLE1 (ASP1) and FLORAL ORGAN NUMBER2 (FON2; Suzuki et al ., 2019b). The CaWUS gene expression also regulates plant width in chickpea, where larger meristem size correlates with larger plant width (Narnoliya et al ., 2019). In tomato, allelic variants of WUS and CLV homologs control locule number and fruit size (Chu et al ., 2019; Muños et al ., 2011).…”
Section: Clavata‐wuschel Signalling: Maintenance Of the Shoot Apical ...mentioning
confidence: 99%
“…Appropriate timing of the transition from vegetative to reproductive growth is highly correlated with crop flowering time and yield (Narnoliya et al, 2019). The morphologic landmark of this change is a protrusion in the peripheral zone, which is called flower primordium (Carles and Fletcher, 2003).…”
Section: Introductionmentioning
confidence: 99%